INFLUENCE ENVIRONMENT WORK AND EMPOWERMENT RESOURCE MAN TO SATISFACTION WORK EMPLOYEE IN PT PNM MEKAR SUKABUMI DISTRICT SUKARAJA UNIT - Dede Lima; Hesri Mentawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The aim of this study is to determine how much big job satisfaction Employees of PT PNM Mekar Sukaraja Unit are influenced by the work environment and human resource empowerment. A quantitative associative research approach aims to analyze the relationship between these factors. The study population consisted of twenty people, all of whom responded using a saturated sampling method. Data collection was conducted with questionnaire scale Likert And analysis data use device soft SPSS version 25. This approach aims to evaluate the influence of each variable partially or simultaneously on employee job satisfaction. Based on the results of the t-test, a significance value of less than 0.05 indicates that the work environment and human resource empowerment variables have a positive and significant impact on employee satisfaction. Work. Temporary That, results test F Which own mark F count as big as 39,492 And a significance value of 0.000 indicates that both factors simultaneously have an influence Which substantial. By Because That, can concluded that improvement work environment and human resource empowerment can significantly increase employee job satisfaction.